A new species of Oxypleurodon Miers, 1886 (Crustacea, Brachyura, Majoidea) from the Bismarck Sea, Papua New Guinea - de Forges, Bertrand Richer; Corbari, Laure (Zootaxa, 2012)
Recently collected specimens from the deep sea off Papua New Guinea revealed the presence of a new species of Oxy-pleurodon Miers, 1886 (Majoidea). The new species is a member of the O. auritum group but its flattened rostral spines and the triangular shape of the carapace easily distinguishes it from congeners.